Acute childhood leukaemia and residence next to petrol stations and automotive repair garages: the ESCALE study (SFCE). Issue 9 (12th February 2009) - Brosselin, P; Rudant, J; Orsi, L; Leverger, G; Baruchel, A; Bertrand, Y; Nelken, B; Robert, A; Michel, G; Margueritte, G; Perel, Y; Mechinaud, F; et al.
Abstract : Background: The association between acute childhood leukaemia and residing next to petrol stations and automotive repair garages was analysed in a national registry-based case–control study carried out in France in 2003–2004. Methods: Population controls were frequency matched with cases on age and gender. Data were collected by standardised telephone interview with the mothers. The latter were asked to report the proximity of their homes to petrol stations, automotive repair garages and other businesses from the conception of the index child to the diagnosis (for cases) or interview (for controls). Odds ratios were estimated using unconditional regression models adjusted for age, gender, number of children under 15 years of age in the household, degree of urbanisation and type of housing. Results: 765 cases of acute leukaemia and 1681 controls were included. Acute leukaemia was significantly associated with residence next to petrol stations or automotive repair garages (OR 1.6, 95% CI 1.2 to 2.2) and next to a petrol station (OR 1.9, 95% CI 1.2 to 3.0). The OR showed no tendency to increase with duration of exposure. The results were not modified by adjustment for potential confounding factors including urban/rural status and type of housing. Conclusions: The results support the findings of our previous study and suggest that living next to a petrol station may be associated with acute childhood leukaemia. The results also suggest that the role of low-level exposure to benzene in acute childhood leukaemia deserves further evaluation.